2019
DOI: 10.1007/s10461-019-02624-3
|View full text |Cite
|
Sign up to set email alerts
|

Slow Acceptance of Universal Antiretroviral Therapy (ART) Among Mothers Enrolled in IMPAACT PROMISE Studies Across the Globe

Abstract: The PROMISE trial enrolled asymptomatic HIV-infected pregnant and postpartum women not eligible for antiretroviral treatment (ART) per local guidelines and randomly assigned proven antiretroviral strategies to assess relative efficacy for perinatal prevention plus maternal/infant safety and maternal health. The START study subsequently demonstrated clear benefit in initiating ART regardless of CD4 count. Active PROMISE participants were informed of results and women not receiving ART were strongly recommended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
1
7
0
1
Order By: Relevance
“…Further, the delay to start taking the medicines after prescription highlights the need to carefully track the immediate start and to support women who may encounter challenges in this early phase. This is congruent with recommendations by a trial conducted at 70 research sites in 15 countries within sub-Saharan Africa, Asia, and the Americas where one-third of asymptomatic HIV positive pregnant and postpartum women did not initiate ART immediately for desire for more time to make a decision [49]. Initiation of Option B+ ART by health providers and actual taking in this study was higher than reported elsewhere [11,12,16].…”
Section: Plos Onesupporting
confidence: 89%
“…Further, the delay to start taking the medicines after prescription highlights the need to carefully track the immediate start and to support women who may encounter challenges in this early phase. This is congruent with recommendations by a trial conducted at 70 research sites in 15 countries within sub-Saharan Africa, Asia, and the Americas where one-third of asymptomatic HIV positive pregnant and postpartum women did not initiate ART immediately for desire for more time to make a decision [49]. Initiation of Option B+ ART by health providers and actual taking in this study was higher than reported elsewhere [11,12,16].…”
Section: Plos Onesupporting
confidence: 89%
“…La actual norma peruana señala que se recomienda el inicio del tratamiento cualquiera sea el estadio clínico (18). No obstante, se deberá evaluar el impacto de esta recomendación, ya que su implementación y aceptabilidad requieren mayor tiempo (27). De la misma manera, el número de casos anuales de sida experimentó una caída significativa y persistente, así como una disminución relevante en la tendencia durante los 14 años posteriores a su implementación.…”
Section: Discussionunclassified
“…Following those findings, all participants in PROMISE were then offered immediate therapy, but only 66% of women not already on ART chose to start after one counselling session. These women needed more time and input to make the decision to initiate therapy [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…New treatment approaches hold promise for addressing some of these retention and adherence concerns. The ARIA Trial showed superior efficacy of dolutegravir/abacavir/lamivudine (DTG/ABC/3TC) fixed-dose combination compared with ritonavir-boosted atazanavir plus tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) in treatment-naïve women [ 10 ] . The dolutegravir-containing regimen was associated with 82% viral suppression at one year, less resistance and lower toxicity [ 11 ].…”
Section: Discussionmentioning
confidence: 99%